Sensitive quantification of the somatostatin analog AP102 in plasma by ultra‐high pressure liquid chromatography–tandem mass spectrometry and application to a pharmacokinetic study in rats. Issue 9 (29th May 2018) - Eugster, Philippe J.; Boyle, Christina N.; Prod'hom, Sylvain; Tarasco, Erika; Buclin, Thierry; Lutz, Thomas A.; Harris, Alan G.; Grouzmann, Eric
Abstract: AP102 is a di‐iodinated octapeptide somatostatin agonist (SSA) designed to treat acromegaly and neuroendocrine tumors. A sensitive and selective method was validated for the quantification of AP102 in plasma following the European Medicines Agency (EMA) and Food and Drug Administration (FDA) guidelines. Sample preparation was performed using solid‐phase extraction microplates. Chromatographic separation was achieved on an ultra‐high pressure liquid chromatography (UHPLC) C18 column in 6.0 minutes. The compounds were quantified using multiple reaction monitoring on a tandem quadrupole mass spectrometer with 13 C, 15 N‐labeled AP102 as internal standard. Calibration ranged from 50 to 10000 pg/mL. The lower limit of quantification (LLOQ) was measured at 20 pg/mL, and robust analytical performances were obtained with trueness at 99.2%–100.0%, intra‐assay imprecision at 2.5%–4.4%, and inter‐assay imprecision at 8.9%–9.7%. The accuracy profiles (total error) built on the 3 concentrations levels showed accuracy within the 70%–130% range. AP102 is remarkably stable since no proteolytic fragments were detected on plasma samples analyzed by Orbitrap‐MS. Pharmacokinetic studies were conducted in rats, after single dose (1, 3, and 10 μg/kg, sc) and continuous subcutaneous administration (osmotic minipumps for 28 days, 3.0 or 10.0 μg/kg/h). AP102 showed a rapid absorption by the subcutaneous route (Tmax : 15–30 minutes) and a fast elimination (t1/2 : 33–86 minutes). The PK profile of AP102 exhibited a mean clearance of 1.67 L/h and a mean distribution volume at steady state of 7.16 L/kg, about 10‐fold higher than those observed with other SSA or non‐ and mono‐iodinated AP102. LogD7.4 determination confirmed the lipophilic properties of AP102 that might influence its distribution in tissues. Abstract : A sensitive and selective method was validated for the quantification by UHPLC–MS/MS of plasma AP102, an octapeptide somatostatin SSTR2/SSTR5 agonist. The lower limit of quantification was measured at 20 pg/mL and imprecision and trueness were within ±10%. Two pharmacokinetic studies were conducted in rats and showed fast absorption and elimination of AP102 with Tmax = 15–30 min, t1/2 = 33–86 min, mean clearance = 1.67 L/h and mean distribution volume at steady state = 7.16 L/kg.